Appendiceal diverticulitis presenting as acute appendicitis and diagnosed after appendectomy - UPRAK, TEVFİK KIVILCIM (My University, 2022)
IntroductionIntroduction Diverticular disease of the appendix (DDA) is a rare appendiceal pathology. It is usually present similar to acute appendicitis. Because of its rarity, the DDA is poorly comprehended. This study evaluates the incidence, clinical and pathological characteristics of appendiceal diverticulitis diagnosed after appendectomy. Methods We performed a retrospective analysis of patients who underwent appendectomy between January 2016 and January 2022 at the Istanbul Sultanbeyli State Hospital General Surgery Clinic. The following parameters were analyzed: age and gender, preoperative diagnosis, laboratory results, radiological imaging findings, surgical technique, histopathological examination of specimens, and complications. Results A total of 1586 patients were analyzed. In the pathology, diverticular disease of the appendix was detected in 10 patients (0.63%). The DDA patients’ mean age was 34.4 years, and the male to female ratio was 4:1. We detected low-grade appendiceal mucinous neoplasia in one of our patients. Conclusion Appendiceal diverticulitis is rare and usually presents as acute appendicitis. Most DDAs are detected incidentally during the postoperative period and are associated with an increased risk of appendiceal neoplasm. Appendectomy specimens should be carefully examined histopathologically to detect diverticular disease of the appendix.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; diverticulosis of the appendix; appendiceal diverticulitis; diverticulitis of the appendix; diverticulitis; appendiceal diverticulosis; appendectomy; acute appendicitis; appendicular diverticulitis; diverticular disease of the appendix; CLINICAL CHARACTERISTICS; DISEASE; : diverticulosis of the appendix; diverticulitis of the appendix; diverticulitis; appendiceal diverticulosis; appendectomy; acute appendicitis; appendicular diverticulitis; diverticular disease of the appendix; diverticulosis of the appendix